2005
DOI: 10.1269/jrr.46.165
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective Property of the Ethanolic Extract of Piper betel Leaf

Abstract: The radioprotective activity of Piper betel ethanolic extract (PE) has been studied using rat liver mitochondria and pBR 322 plasmid DNA as two model in vitro systems. The extract effectively prevented gamma-ray induced lipid peroxidation as assessed by measuring thiobarbituric acid reactive substrates, lipid hydroperoxide and conjugated diene. Likewise, it prevented radiation-induced DNA strand breaks in a concentration dependent manner. The radioprotective activity of PE could be attributed to its hydroxyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 22 publications
1
42
0
2
Order By: Relevance
“…Thus, there is a need to develop anti-allergic agents from natural sources such as edible or medicinal plants. The importance of ethnomedicines is increasing due to their low cost, frequently easy accessibility and low toxicity, and almost half of current pharmaceuticals originate from plant products [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a need to develop anti-allergic agents from natural sources such as edible or medicinal plants. The importance of ethnomedicines is increasing due to their low cost, frequently easy accessibility and low toxicity, and almost half of current pharmaceuticals originate from plant products [10].…”
Section: Discussionmentioning
confidence: 99%
“…As well as use as a mouth freshener, the leaves are used for wound healing [3] and digestive and pancreatic lipase stimulant activities in traditional medicine [4]. Antioxidant [5,6], anti-bacterial and anti-fungal [1,[7][8][9], antiinflammatory [10], anti-diabetic [11] and radioprotective [10] activities of P. betle have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicate hydroxychavicol as an antimutagenic agent (12,23) as well as an effective inhibitor of cyclooxygenase (COX), platelet calcium signaling, and thromboxane B2 production (21). Other studies suggest that hydroxychavicol also known as APC possesses antiulcerogenic activity (24) and has been shown to alleviate indomethacin-induced stomach ulceration leading to gastric cancer (25). Hydroxychavicol also inhibits inflammatory response molecules like inducible nitric oxide synthase and COX-2, which are known to enhance tumor growth by downregulation of the NF-kB) pathway (24).…”
Section: Betel Leaves: Abundant Repositories Of Cancer-fighting Phytomentioning
confidence: 99%
“…Hydroxychavicol also inhibits inflammatory response molecules like inducible nitric oxide synthase and COX-2, which are known to enhance tumor growth by downregulation of the NF-kB) pathway (24). Chavibetol (CHV), along with hydroxychavicol, acts as a radioprotectant (25), and exhibits substantial immunomodulatory and free radical scavenging activities (25). We have shown that CHV synergizes with hydroxychavicol to exert antiproliferative activity against human prostate cancer PC-3 cells (20).…”
Section: Betel Leaves: Abundant Repositories Of Cancer-fighting Phytomentioning
confidence: 99%
“…The leaves have a strong, pungent, aromatic flavour and are widely chewed for the production of the juice by the natives of India, Sri Lanka, Taiwan, and Malaysia [11]. PB has many medicinal properties, such as antibacterial, antifungal, antitumour, and anti-inflammatory characteristics [12,13,14]. It was also shown to have high antioxidant capacity and contains several phenolics, such as hydroxycavicol, eugenol, cevibetol, and alylpyrocatechol, which may contribute to most of the biological properties seen in the leave extract [15].…”
Section: Introductionmentioning
confidence: 99%